Management Transformation in Family Businesses in Palm Oil Plantations: From Independent Management to Professional and Structured Organizations - Rial Nanda Putra, Dhaffin (Syntax Corporation, 2026)
The family owned industry is still very strong in the agribusiness industry in Indonesia, especially in the palm oil industry. Although they are economically important, there are structural and managerial problems in most family-run plantations that are due to traditional and informal forms of managing them. This paper explores how job analysis and human capital management (HCM) may be used to achieve management change and sustainability of succession in a palm oil plantation owned by a family in North Sumatra. The study bases its methodology on the qualitative case study, and was backed with scanty quantitative data concerning productivity and workforce structure. In-depth interviews with the owners of the plantations, family members, and key employees were used as primary data collection methods where field observation and analysis of documents were also used as supplementary methods. Based on the structure in Braun and Clarke (2006) framework, thematic analysis was used to extract common themes in terms of job roles, leadership succession, and professionalization initiatives. Results indicate that unplanned job analysis translates to lack of clarity of job responsibilities, duplication of duties, and inconsistency in resolution of duties at various levels. The combination of job analysis and HCM models like competency-based job design, performance appraisal framework, and talent management will greatly improve organizational performance and equip the organization with the transition to generational leadership. The succession planning is also recognized by the study as a decisive factor of sustainable change, which correlates with theoretical approaches in the family business theory, socioemotional wealth, and development of human capital. The study is helpful in comprehending how family-run agribusiness can be transformed into professionally run enterprises without losing socioemotional and legacy values of such enterprises. As shown in the proposed framework, job analysis is an effective framework on which to base the restructuring of human capital systems, leadership succession, and competitiveness in the long term in the palm oil industry owned by families in Indonesia.